THE IMPACT OF ADVERSE DRUG REACTION OCCURRENCE TO DRUG ADHERENCE LEVEL: A CROSS-SECTIONAL STUDY IN PATIENTS WITH TUBERCULOSIS - Bakri, Tedy Kurniawan; Akmal, Raihanul; Vonna, Azizah; Sari, Fitrah (JURNAL FARMASI GALENIKA, 2021)
Tuberculosis is well-known as an ancient disease that remains a global challenge until this era. The main goals of the treatment are to eradicate the colonization of acid-resistant basil and to prevent the occurrence of drug resistance. However, the accomplishment of this multi-drugs therapy is not always achieved due to several obstacles, one of is patient adherence to the treatment. Patient adherence is a considerable determinator that influenced by a number factors including the adverse drug reaction (ADR) which appeared to the patients. This study aimed to examine the correlation between adverse drug reaction and patients’ adherence to the anti-tuberculosis category 1 regimen during the intensive phase. This observational analytic study used cross sectional method and involved 35 subjects. Drug adherence level was measured using Medication Adherence Scale-8 (MMAS-8) questionnaire, the characteristics of ADR were collected using check list sheet of ADR, and the probability of ADR was analyzed using Naranjo Algorithm. The results showed that the majority of patients in this study were adherence to anti tuberculosis drugs (62,8%) and experienced ADR (74,3%). Bivariate analysis using chi-square statistical test showed there was significant correlation between adverse drug reaction and adherence to anti-tuberculosis drugs during the intensive phase treatment (P-value = 0,02288).